Case Report: Personalized management of HER2-positive breast cancer with advanced nodal disease during pregnancy: a clinical case and review - Gullotta, Carla; Walbaum, Benjamin; Seguí, Elia; López, Marta; Mension, Eduard; Cebrecos, Isaac; Molla, Meritxell; Oses, Gabriela; Bargalló, Xavier; Ganau-Macias, Sergi; Sanfeliu, Esther; Braso-Maristany, Fara; et al. (Frontiers in Oncology, 2026)
BackgroundPregnancy-associated breast cancer (PrBC) poses complex challenges in diagnosis and treatment, particularly when associated with biologically aggressive subtypes and extensive nodal involvement. Management must be individualized, integrating oncologic urgency, fetal safety, and limited validated evidence in this unique setting.Case SummaryWe present the case of a 36-year-old woman diagnosed during the second trimester of pregnancy with HER2-positive (HER2+), node-positive (cT2[m]N3a) breast cancer (BC). After a multidisciplinary team discussion, patient initiated anthracycline- and taxane-based neoadjuvant chemotherapy during gestation. Given its contraindication during pregnancy, anti-HER2 therapy was added postpartum, and surgery included nipple-sparing mastectomy with targeted axillary dissection (TAD) of clipped nodes. Pathology revealed minimal residual invasive disease in the breast and a complete axillary response, allowing omission of axillary lymph node dissection (ALND). Genomic profiling with HER2DX supported high-risk disease and informed systemic therapy with delayed anti HER2 therapy, and conservative axillary management (TAD without ALND) in cT2N3 PrBC, without compromising fetal outcome. The patient subsequently received adjuvant chest wall and nodal region radiotherapy plus trastuzumab-emtansine (T-DM1).ConclusionThis case underscores the value of personalized, multidisciplinary management in PrBC, particularly in patients with high-risk biologic features and advanced nodal disease. Integrating clinical judgment, genomic tools, and adaptive strategies, while accounting for gestational limitations, can optimize oncologic outcomes without compromising fetal safety.